2016
DOI: 10.1017/hpl.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

Avalanche boron fusion by laser picosecond block ignition with magnetic trapping for clean and economic reactor

Abstract: (2015)) for the combination of the non-thermal block ignition using ultrahigh intensity laser pulses of picoseconds duration. The ultrahigh acceleration above 10 20 cm s −2 for plasma blocks was theoretically and numerically predicted since 1978 (Hora, Physics of Laser Driven Plasmas (Wiley, 1981), pp. 178 and 179) and measured (Sauerbrey, Phys. Plasmas 3, 4712 (1996)) in exact agreement (Hora et al., Phys. Plasmas 14, 072701 (2007)) when the dominating force was overcoming thermal processes. This is based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Though details of the clean and low-cost laser boron fusion reactor have been discussed before (Hora et al, 2017a(Hora et al, , 2017b(Hora et al, , 2017c, the following points should be underlined. The reaction unit in the center of the reaction sphere ( Fig.…”
Section: Design Of Laser Boron Fusion Reactormentioning
confidence: 99%
See 1 more Smart Citation
“…Though details of the clean and low-cost laser boron fusion reactor have been discussed before (Hora et al, 2017a(Hora et al, , 2017b(Hora et al, , 2017c, the following points should be underlined. The reaction unit in the center of the reaction sphere ( Fig.…”
Section: Design Of Laser Boron Fusion Reactormentioning
confidence: 99%
“…These details are also of importance when the nonlinear force acceleration process in target layers is used for the generation of space charge neutral ion beams, with more than million times higher ion densities than the best classical accelerator can produce (Hora et al, 2017a(Hora et al, , 2007 for ion energies of few hundred MeV energy cancer treatment or for space craft propulsion (Hora et al, 2011;Lalousis et al, 2013;Hoffmann et al, 2018). Even nearly monoenergetic proton beams above GeV (Xu et al, 2016; It is shown in the 2nd and 3rd Sections that the ultrahigh plasma-block acceleration is the essential mechanism for the non-LTE process of the low-temperature ignition (Hora et al, 2015(Hora et al, , 2017a(Hora et al, , 2017b(Hora et al, , 2017c of the laser boron fusion for the new reactor design. This was possible only by the extreme contrast ratio (Danson et al, 2018) of the laser pulses as it was realized in retrospect only (Hora, 2016) by the blue Doppler shift of spectral lines (Sauerbrey, 1996;Zhang et al, 1998;Földes et al, 2000).…”
Section: Design Of Laser Boron Fusion Reactormentioning
confidence: 99%
“…It goes without saying that the capability to achieve a chain reaction with multiplicity 𝑘 ≳ 1 would play a significant -if not indispensable -role in the possible exploitation of H 11 B fusion for energy production purposes, especially under laser-driven schemes for plasma generation and confinement (Hora et al, 2015(Hora et al, , 2016(Hora et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The boron-to-hydrogen ion concentration used is unclear (perhaps 8.9%, the optimum for thermonuclear ignition); moreover, only the Coulomb interaction was taken into account in the α-ion scattering, neglecting the nuclear (hadronic) one, which can instead turn out to be predominant, as we shall see. Recently, Hora et al (2015Hora et al ( , 2016 and Eliezer et al (2016) have claimed evidence of the chain reaction in experiments at the Prague Asterix Laser System (PALS), Czech Republic, where an unprecedented fusion yield (4×10 8 α's per laser pulse) had been achieved by irradiation of an H-enriched, B-doped Si target (Picciotto et al, 2014;Margarone et al, 2015). On the contrary, Shmatov (2016) and Belloni et al (2018) have refuted this possibility on the basis of stopping power and α-p collision rate arguments.…”
Section: Introductionmentioning
confidence: 99%
“…In this plasma, the ion and hot-electron components are capable of giving some number of fusions. The use of specific targets may increase this number considerably [22][23][24], and this is thought to be due to resonance phenomena [33][34][35][36]. • Scheme 2.…”
Section: Introductionmentioning
confidence: 99%